AN ANALYSIS OF SPEAKING CLASSROOM DISCOURSE BASED ON CDA BY MEANS OF FAIRCLOUGH’S FRAMEWORK - Pipih Nofitasari (Journal of English Education Program (JEEP), 2017)
This is a qualitative research that draws on Fairclough’s Critical Discourse Analysis methodology to analyze the speaking classroom discourses in one of senior high school in Ciamis. The study involved one English teacher and students at the tenth grade especially class X3. The aim of this study is to display the important contribution which a critical analysis makes to our understanding of teacher/students relationship through the analysis of critical discourse analysis. The data source consists of transcripts by applying three steps within CDA (description, interpretation, and explanation), indicated that some textual formal features were dominant, besides  teacher have dominant role to the extend that the students were keep apparently passive and powerless. The finding of this study are expected for teacher and students in increasing their critical thinking towards phenomena or social practice around them.